2022
DOI: 10.1111/cns.13771
|View full text |Cite
|
Sign up to set email alerts
|

Recent highlights in periopeative neurological disorders, from bench to bedside

Abstract: Perioperative neurological disorders are important causes of postoperative disability and even perioperative death, bringing a huge challenge to the vulnerable and increasing aging population. Perioperative neurological disorders usually contain ischemic stroke, hemorrhagic stroke, and neurocognitive disorders during the perioperative period. Although a few prevention and treatment strategies have been developed for each disorder, there is still a lack of effective treatments and the underlying mechanisms are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…An individualized treatment approach is recommended based on types of malignancies and stroke severities. [90][91][92][93] Moreover, MAS patients with Trousseau syndrome typically have poor survival. Therefore, there is a need to determine the effectiveness of rehabilitation treatment and develop a comprehensive treatment strategy earlier than that in the general stroke population.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…An individualized treatment approach is recommended based on types of malignancies and stroke severities. [90][91][92][93] Moreover, MAS patients with Trousseau syndrome typically have poor survival. Therefore, there is a need to determine the effectiveness of rehabilitation treatment and develop a comprehensive treatment strategy earlier than that in the general stroke population.…”
Section: F I G U R Ementioning
confidence: 99%
“…An individualized treatment approach is recommended based on types of malignancies and stroke severities. 90 , 91 , 92 , 93 …”
Section: Therapeutic Options For Mas Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…258 Therefore, intervention targeting perioperative inflammation may be effective in the prevention. 259 A 2020 meta-analysis included 8 randomized trials with 1106 patients preparing for orthopedic surgery; the results showed that perioperative parecoxib administration decreased the incidence of delayed neurocognitive recovery and improved Mini-Mental Examination score early after surgery. 260 Parecoxib should be considered in highrisk patients without contraindications.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Peripheral inflammation provoked by anesthetic exposure and surgery can induce blood–brain barrier disruption 257 ; the resulting neuroinflammation is found to be an important underlying mechanism of perioperative NCDs 258 . Therefore, intervention targeting perioperative inflammation may be effective in the prevention 259 . A 2020 meta‐analysis included 8 randomized trials with 1106 patients preparing for orthopedic surgery; the results showed that perioperative parecoxib administration decreased the incidence of delayed neurocognitive recovery and improved Mini‐Mental Examination score early after surgery 260 .…”
Section: Prevention For Perioperative Ncdsmentioning
confidence: 99%